Cardiac involvement in Anderson–Fabry disease. (24th August 2010) - Cauti, Filippo Maria; O'Mahony, Constantinos; Pantazis, Antonis
Abstract : A normotensive 50-year-old man was evaluated for cardiac symptoms associated with left ventricular hypertrophy (LFH). His symptoms were caused by cardiac involvement from Anderson–Fabry disease (AFD), an X linked lysosomal storage disease caused by mutations in the GLA gene which encodes for the lysosomal enzyme -galactosidase A. He was treated with recombinant enzyme but the clinical course was complicated by arrhythmias and the patient required an internal cardioverter defibrillator. Even though AFD is rare, this case illustrates the importance of considering the diagnosis in selected patients as effective treatment has recently become available. Recognition of AFD also allows for screening of asymptomatic relatives who may benefit from treatment before irreversible life-threatening complications develop.